WOMEN ENTREPRENEURSHIP: A ROAD AHEAD - Patil, Prachita; Deshpande, Yogesh (FEB - Universitas Lampung, 2018)
In today’s century, women are playing multitasking role and thus have become an important nutshell of global environment which is a necessity for economic development and social progress. In order to achieve equal rights, identity and position in society educated women have to go long way despite all traditional barriers for them in their respective fields. The variation of Social fabric in the Indian society in terms of varied inspirations and increased educational status of women for better living necessitated a change in lifestyle of Indian women. As women they have to face cut-throat competition with man in every prospect, a business is no longer for them indeed balancing both family and work life. The main purpose of this paper is to highlight the status of women entrepreneurs in India and also includes prospects and reasons which uplift them behind the women entrepreneurship. Another main purpose of this paper is to analyze policies of Indian government for women and also schemes adequately for the growth of women entrepreneurship. On the basis of this study, some suggestions are given to motivate and to enhance women to become a successful entrepreneur.